What do we know about carbon disclosure? A bibliometric analysis - Doddy Setiawan; Arif Santoso; Andi Asrihapsari; Rayenda Khresna Brahmana; Amar Hisham Jaaffar (Cogent Social Sciences)
Climate change is a global risk that drives extensive research, including carbon disclosure. Although the field has grown significantly over the past two decades, there are remains gaps in comprehensive reviews. Therefore, this review aimed to provide an updated summary of the literature on carbon disclosure. A total of 278 articles were selected from the Scopus database, covering the period from 2004 to 2024. Co-author and co-word analyses were conducted using VOSViewer and Bibliometrix R-Packages. The review successfully identified the most relevant authors, sources, countries, and affiliations related to carbon disclosure. It also analyzed the intellectual structure, influential journal, thematic evolution, trend topics, and selective data sources, as well as theoretical foundations in the field. Several investigations have focused on evaluating some aspects of disclosure such as its quantity and quality, determinants, as well as beneficial effects. The current review identified the most relevant topics for future surveys, including companies governance and greenwashing. Additionally, it contributed to the existing body of empirical literature by providing an updated summary and addressing the gaps and limitations in previous investigations, particularly in methodology, data acquisition, and review methods.